Perilaku Belajar, Minat Belajar dan Tingkat Pemahaman Akuntansi dengan Pembelajaran Daring sebagai Variabel Mediasi - Waloka, Made Swari Praba; Juliarsa, Gede (E-Jurnal Akuntansi; Vol 31 No 10 (2021)DO - 10.24843/EJA.2021.v31.i10.p11, 2021)
This study aims to determine the effect of learning behavior and interest in learning on the level of understanding of accounting and the role of online learning in mediating the influence of learning behavior and interest in learning on the level of accounting comprehension. This research was conducted at the Faculty of Economics and Business, Udayana University. The sampling technique used was purposive sampling method, the number of samples obtained was 90 samples. The analysis technique used is path analysis. Based on the results of the analysis, it was found that learning behavior had no significant effect on the level of accounting understanding of students. Interest in learning and online learning has a significant effect on the level of accounting understanding. Online learning is significantly able to mediate the effect of learning behavior and interest in learning on the level of accounting understanding of students. Keywords: Learning Behavior; Learning Interest; Online Learning; Accounting Understanding.